Recibir la reparación. Aproximación a dos organizaciones de desplazados del conflicto armado interno en Lima y su acceso a reparaciones colectivas - Ramírez Zapata, Ivan Andres (2018)
This article illustrates the characteristics of two Lima-based organizations of persons displaced by the internal armed conflict in Peru (1980-2000), and the way in which these characteristics create opportunities and obstacles for access to the Program of Collective Reparations —a key element of the Peruvian reparations policy—. This program provides funding to a collective beneficiary for institutional strengthening or economic entrepreneurship.Based on bibliographic review, interviews with members of these organizations as well as ethnographic field work, I show that the  characteristics of each displaced persons’ organization together with the type of collective project they choose create scenarios of challenges and possibilities which pose difficulties to these groups, requiring collective action capacities which they do not necessarily have. This results in a de facto situation that undermines their right to reparation. Therefore, I argue the importance not only of analizing the reparations offer and its quality, but also the characteristics of the demand, that is, of the beneficiary groups of displaced persons and their internal interactions, and how these factors shape access to reparations.